Impact Evaluation of Social Funds : An Introduction - Rawlings, Laura B.; Schady, Norbert R. (Washington, DC: World Bank, 2014)
Despite the importance of knowing whether development programs achieve their objectives, impact evaluations remain rare in developing economies. This is unfortunate. With the growing use of results-based management by governments, determining whether goals have been attained and convincingly linking changes to specific programs has become increasingly critical. Tracking such outcomes as gains in school enrollment or reductions in infant mortality is indispensable. But simply gathering good data on outcomes sheds little light on why objectives have or have not been met. For this reason, impact evaluations should be a key instrument in policymakers' monitoring and evaluation toolbox.